2023
DOI: 10.21203/rs.3.rs-2527169/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robotic Pendant Drop: Containerless Liquid for μs-resolved, AI-executable XPCS

Abstract: X-ray Photon Correlation Spectroscopy (XPCS) probes the spontaneous fluctuation in spatial configurations of mixed phases, which can significantly impact the material properties of complex fluid. Tailored material design, however, requires navigation through massive multi-dimensional parameter space which is beyond the bandwidth of current XPCS beamline infrastructure. Using 3.7 μs-resolved XPCS, we demonstrate that Brownian dynamics of silica colloidal nanoparticles in a shielded pendant drop suspended from a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Robotic pendant drop provides an end-to-end automated, msresolved XPCS workow for studying the dynamics and structures of complex uids. Ozgulbas et al 65 recently demonstrated that Brownian dynamics of nanoparticle colloid in a pendant drop is consistent with the reference setup such as thin-walled quartz capillaries. Furthermore, the pendant drop setup can be integrated with a robotic arm (UR3e) to fully automate sample preparation, characterization, and disposal.…”
Section: Pendant Drop For Study Of Complex Uidssupporting
confidence: 65%
“…Robotic pendant drop provides an end-to-end automated, msresolved XPCS workow for studying the dynamics and structures of complex uids. Ozgulbas et al 65 recently demonstrated that Brownian dynamics of nanoparticle colloid in a pendant drop is consistent with the reference setup such as thin-walled quartz capillaries. Furthermore, the pendant drop setup can be integrated with a robotic arm (UR3e) to fully automate sample preparation, characterization, and disposal.…”
Section: Pendant Drop For Study Of Complex Uidssupporting
confidence: 65%